Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1103/physrevlett.95.185703
|View full text |Cite
|
Sign up to set email alerts
|

Counterions at Charged Cylinders: Criticality and Universality beyond Mean-Field Theory

Abstract: The counterion-condensation transition at charged cylinders is studied using Monte-Carlo simulation methods. Employing logarithmically rescaled radial coordinates, large system sizes are tractable and the critical behavior is determined by a combined finite-size and finite-ion-number analysis. Critical counterion localization exponents are introduced and found to be in accord with mean-field theory both in 2 and 3 dimensions. In 3D the heat capacity shows a universal jump at the transition, while in 2D, it con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
115
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(124 citation statements)
references
References 25 publications
(31 reference statements)
9
115
0
Order By: Relevance
“…This qualitative picture is actually supported by existing analytical results of mean-field [89,90] and strong-coupling [71] theory; both limiting theories give the same threshold of ξ * = 1. Recent numerical simulations [91] show that this threshold is in fact universal and holds in all ranges of the coupling parameter Ξ. Moreover, the threshold counterion-condensation process at charged cylinders exhibits a set of scaling relations, which are characterized by universal exponents [91].…”
Section: A Binding-unbinding Transition Of Counterionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This qualitative picture is actually supported by existing analytical results of mean-field [89,90] and strong-coupling [71] theory; both limiting theories give the same threshold of ξ * = 1. Recent numerical simulations [91] show that this threshold is in fact universal and holds in all ranges of the coupling parameter Ξ. Moreover, the threshold counterion-condensation process at charged cylinders exhibits a set of scaling relations, which are characterized by universal exponents [91].…”
Section: A Binding-unbinding Transition Of Counterionsmentioning
confidence: 99%
“…Recent numerical simulations [91] show that this threshold is in fact universal and holds in all ranges of the coupling parameter Ξ. Moreover, the threshold counterion-condensation process at charged cylinders exhibits a set of scaling relations, which are characterized by universal exponents [91].…”
Section: A Binding-unbinding Transition Of Counterionsmentioning
confidence: 99%
“…To our problem, we acknowledge the published works from Naji and Netz [26,27] and Burak and Orland [2], which have covered thoroughly the basics of the two dimensional construction of the cell model. They observed that condensation obeys the well-known threshold at ξ = 1 where below this value there is none.…”
Section: Introductionmentioning
confidence: 99%
“…Here the familiarized reader may have noticed that for the two dimensional systems it is accustomed to use Γ for the notation of the coupling constant [3,6,7,29,30]; the previous defined coupling equates the standardized one as Ξ = Γ/2, but we have kept Ξ motivated by a discussion with the three dimensional case. Finally the third parameter, defined as ∆ = log(D/R), which measures in log-scale the size of the system.To our problem, we acknowledge the published works from Naji and Netz [26,27] and Burak and Orland [2], which have covered thoroughly the basics of the two dimensional construction of the cell model. They observed that condensation obeys the well-known threshold at ξ = 1 where below this value there is none.…”
mentioning
confidence: 99%
See 1 more Smart Citation